ANALISIS CAKUPAN SITUS-SITUS PERMUKIMAN NEOLITIK DI BANYUWANGI SELATAN - Sofwan Noerwidi (Balai Arkeologi Yogyakarta, 2013)
Economic calculations as cost-benefit ratios are used by prehistoric people in exploiting their natural resources. This paper will discuss about landscape and natural resources to reconstruct the site catchment area which explored by Neolithic people at South Banyuwangi in prehistoric times. In the Site Catchment Analysis for traditional farmer, a preliminary of 1-km radius site catchment zone is the most basic or regular subsistence resources, and 5-km radii is largely the maximum limits of radius distance. Based on hypotheses of catchment zone, we analyzed its natural resource inside eachcatchment zone. This analysis conducted on landscape conditions (hills, plains, steep cliffs), water sources (springs, rivers and water basins). Comparison between environmental conditions inside the catchment zone and artifact findings (from survey and excavation work) is obtained to predict the site catchment pattern of Neolithic settlement sites at South Banyuwangi.